Edward Elgar and His World - Adams, Byron (Book collections on Project MUSE., 2007)
Edward Elgar (1857-1934) is undoubtedly one of the most fascinating, important, and influential figures in the history of British music. He rose from humble beginnings and achieved fame with music that to this day is beloved by audiences in England, and his work has secured an enduring legacy worldwide. Leading scholars examine the composer's life in Edward Elgar and His World, presenting a comprehensive portrait of both the man and the age in which he lived. Elgar's achievement is remarkably varied and wide-ranging, from immensely popular works like the famous Pomp and Circumstance March no. 1--a standard feature of American graduations--to sweeping masterpieces like his great oratorio The Dream of Gerontius . The contributors explore Elgar's Catholicism, which put him at odds with the prejudices of Protestant Britain; his glorification of British colonialism; his populist tendencies; his inner life as an inspired autodidact; the aristocratic London drawing rooms where his reputation was made; the class prejudice with which he contended throughout his career; and his anguished reaction to World War I. Published in conjunction with the 2007 Bard Music Festival and the 150th anniversary of Elgar's birth, this elegant and thought-provoking volume illuminates the greatness of this accomplished English composer and brings vividly to life the rich panorama of Victorian and Edwardian Britain. The contributors are Byron Adams, Leon Botstein, Rachel Cowgill, Sophie Fuller, Daniel M. Grimley, Nalini Ghuman Gwynne, Deborah Heckert, Charles Edward McGuire, Matthew Riley, Alison I. Shiel, and Aidan J. Thomson.